Comparison of the postoperative analgesic effects of paracetamol–codeine phosphate and naproxen sodium–codeine phosphate for lumbar disk surgery. Issue 9 (6th August 2015) - Polat, Reyhan; Peker, Kevser; Gülöksüz, Çiğdem Topçu; Ergil, Julide; Akkaya, Taylan
Abstract: The aim of this study was to compared the efficacy of paracetamol–codeine phosphate and naproxen sodium–codeine phosphate on postoperative pain and tramadol consumption during the first 24 hours after a lumbar disk surgery. After Ethics Committee approval and informed consent had been obtained, 64 patients were allocated into three groups. Patients received oral paracetamol–codeine (300 mg + 30 mg; Group P), naproxen sodium–codeine (550 mg + 30 mg; Group N), or placebo tablets (Group C) 30 minutes prior to induction of anesthesia. Patient‐controlled analgesia was supplied postoperatively using tramadol. Pain intensity, tramadol consumption, and side effects were recorded every 1 hour, 2 hours, 6 hours, 12 hours, and 24 hours after surgery. Whole study period pain intensity (visual analogue scale scores) was lower in Group P ( p = 0.007) and Group N ( p = 0.001), compared with Group C, however, there was no statistically significant difference between Group P and Group N regarding pain intensity ( p > 0.05). Tramadol consumption was lower in Group P and Group N, compared with Group C ( p < 0.001), and in turn the lowest incidence of tramadol consumption was detected in Group P compared with Group N ( p < 0.001) and Group C ( p < 0.001). Side effects were similar between the groups. Preemptive administration of paracetamol–codeine and naproxen sodium–codeine combination significantly reduced tramadol consumption and provided more effective analgesia compared with placebo. The paracetamol–codeine combination was superior to naproxen sodium–codeine with regard to tramadol consumption.